Contrast‐enhanced ultrasound combined with augmented reality medical technology in the treatment of rabbit liver cancer with high‐energy focused knife. (20th April 2021) - Na, Fengyu; Wang, Li; Wu, Cuicui; Ding, Yan
Abstract: Augmented reality technology can enhance people's perception and interactive experience of real scenes due to its characteristics of fusion of virtual and real, and has become a popular technology in the field of computer science. This article mainly studies the application of contrast‐enhanced ultrasound combined with augmented reality medical technology in the treatment of rabbit liver cancer with high‐energy focused knife. Sixty healthy male New Zealand white rabbits were used in this study. Seldinger's method was used to superselective embolize the artery supplying tumor with the help of hepatic angiography, which can kill tumor cells to the greatest extent and reduce the damage to normal liver cells. At the same time, another assistant under the guidance of ultrasound inserted the temperature probe into the position 1 cm away from the microwave radiation source, and then started the microwave ablation (MWA) treatment. High intensity focused ultrasound (HIFU) treatment is carried out under general anesthesia, the breathing rhythm of patients is controlled by ventilator, the proper position is set before operation, the real‐time monitoring is carried out by ultrasound monitoring mediated by medium water, and the HIFU three‐dimensional scanning treatment system is used to accurately cover all tumor treatment areas from point to line and from line to surface, so as to kill tumor cells to the greatest extent. The data of each group were processed by SPSS17.0 statistical software, and the measurement data were expressed as mean ± SD. ANOVA analysis of variance was used to compare the differences among the groups, and LSD method was used to make pairwise comparison within the group. p < 0.05 was considered as having statistical difference. The growth rate of tumor was 56.1% and 60.3%, respectively. Contrast‐enhanced ultrasound combined with augmented reality medical technology provides a new way for the treatment of rabbit liver cancer.